Electromyographic analysis of elite para table tennis players with complete and incomplete spinal cord injury during forehand loop and backhand - Norouzi, M.; Ardakani, M. K.; Mahmoudkhani, M.; Dibafar, M. (Research Square, 2023)
Background: Para table tennis is a popular sport among individuals with disabilities, and each Paralympic sport has its own classification system. This classification aims to minimize the impact of impairments caused by disability on athletic performance. In the present study, the electromyographic variables of the muscles involved in performing the forehand loop and backhand techniques of elite para table tennis players with complete and incomplete spinal cord injuries in the class 5 category were compared. Methods: In this study, there were 20 male participants at the national level. According to the ASIA scale, the participants were divided into two groups of 10 people. The first group had complete spinal cord injury, while the second group had incomplete spinal cord injury. After they entered the laboratory, the electrodes were connected to their deltoid, biceps, external oblique, and erector spinae muscles. After connecting the electrodes, the tasks were performed and muscles` EMG activity, as well as their onset and offset contraction were monitored. Results: The findings revealed that there are significant differences in the amount of EMG activity as well as the timing of the onset and offset of contraction of selected muscles in two groups of complete and incomplete spinal cord injuries. Conclusion: The findings suggest that athletes with incomplete spinal cord injuries may perform better than those in the complete group. However, current para table tennis classification rules place both groups in the same class, which could impact the outcome of matches.